A method for recovering and repairing defective lithium iron phosphate products

Through the composite technology of solid electrolyte and carbon materials, the complex process and high energy consumption in the recycling and repair of lithium iron phosphate residues is solved, and efficient resource recovery and battery performance optimization are achieved.

CN119764641APending Publication Date: 2025-04-04云南烨阳新能源材料有限责任公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411928803.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art has complicated processes and high energy consumption when recycling and repairing lithium iron phosphate residues, making it difficult to achieve efficient resource recovery and performance optimization.

Method used

Solid electrolyte raw materials, supplemented with lithium, phosphorus and iron sources, combined with carbon sources and complexing agents, are used to prepare the reaction sol, and after stirring, drying and multi-stage sintering, lithium iron phosphate/solid electrolyte/carbon composite material is formed.

Benefits of technology

It realizes efficient repair of lithium iron phosphate residues, improves the electronic conductivity and ionic conductivity of the material, enhances the rate performance and stability of the battery, and promotes the recycling of resources.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for recovering and repairing defective lithium iron phosphate products, and relates to the technical field of functionalized reuse of lithium iron phosphate. The invention comprises the following steps: S1. After dissolving solid electrolyte raw materials, supplementary lithium sources, supplementary phosphorus sources and supplementary iron sources in sequence, supplementary carbon sources and complexing agents are added to prepare reaction sol; S2. The purified lithium iron phosphate waste powder is added to the reaction sol, stirred to form a pre-sizing material; S3. The pre-sizing material is dried, sintered in multiple stages, and crushed to obtain a lithium iron phosphate / solid electrolyte / carbon composite material as a repaired finished product; so as to achieve the purpose of completing the value assignment recovery of defective lithium iron phosphate waste in one step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functionalized recycling of lithium iron phosphate, and in particular to a method for recycling and repairing defective lithium iron phosphate products. Background Art

[0002] Lithium iron phosphate has an olivine structure, with a theoretical specific capacity of 170 mAh / g, a cycle number of more than 6,000, and stable performance, safety, environmental protection, and low price. Lithium iron phosphate batteries are widely used due to their high energy density, good stability, and low cost. However, there is a problem of defective waste powder in the production and use of lithium iron phosphate. First, with the rapid development of electric vehicles, portable electronic devices, and renewable energy storage systems, the demand for lithium iron phosphate batteries continues to rise.

[0003] At the same time, the new energy market will also face a huge problem of scrapped batteries, and a large amount of lithium iron phosphate waste powder to be processed may cause environmental pollution. In addition, during the experiment and large-scale production of lithium iron phosphate, it is inevitable that defective and unqualified lithium iron phosphate products will be generated, which will be manifested in low electronic conductivity and ion conductivity, thus affecting its high capacity, long cycle and high rate performance.

[0004] Secondly, in the process of preparing lithium iron phosphate pole pieces into batteries, waste pole pieces and broken pieces will be produced. If they are discarded at will, a large amount of resources will be wasted. Therefore, it is possible to consider reusing the separated positive electrode materials. Therefore, in recent years, there is an urgent need for economical and efficient recycling and processing technology for lithium iron phosphate positive electrode materials, so as to recycle lithium, iron and phosphorus resources, realize the repair of lithium iron phosphate waste powder, and reuse lithium iron phosphate positive electrode materials in the battery field.

[0005] At present, the recycling of discarded batteries and defective products in the industry is mostly achieved through wet chemical and pyrometallurgical methods to recycle lithium, iron and phosphorus related compounds, obtain battery-grade raw materials such as lithium carbonate, FePO4 and Fe2O3, and further go through a series of process flows to obtain qualified lithium iron phosphate positive electrode materials; the process is complicated and energy-intensive. Summary of the invention

[0006] The purpose of the present invention is to provide a method for recovering and repairing defective lithium iron phosphate products, so as to achieve the purpose of completing the value-added recovery of defective lithium iron phosphate waste products in one step.

[0007] In order to achieve the above object, the present invention adopts the following technical means: A method for recovering and repairing defective lithium iron phosphate products comprises the following steps: S1. After dissolving the solid electrolyte raw material, the supplementary lithium source, the supplementary phosphorus source and the supplementary iron source in sequence, a supplementary carbon source and a complexing agent are added to obtain a reaction sol; S2. The purified lithium iron phosphate waste powder is added to the reaction sol and stirred to form a pre-sizing material; S3. Dry the pre-sizing material, perform multi-stage sintering, and then crush it to obtain a lithium iron phosphate / solid electrolyte / carbon composite material as a repaired product.

[0008] Preferably, the solid electrolyte raw material includes one of an oxide solid electrolyte, a sulfide solid electrolyte and a halide electrolyte; The oxide solid electrolyte includes any one of a NASICON solid electrolyte, a garnet solid electrolyte, and a perovskite solid electrolyte; The sulfide solid electrolyte includes Li 10 GeP2S 12 、Li6PS5Cl、Li 10 S N 12 , one or more of Li2S-P2S5, Li2S-SiS2 and Li2S-B2S3; The halide solid electrolyte includes one or more of Li3YCl6, Li3ErCl6, Li3YBr6, Li3InBr and Li3InCl6.

[0009] Further, the supplementary lithium source includes one or more of Li2CO3, LiOH, LiHPO4, LiNO3, lithium acetate, lithium citrate, LiF and LiCl; The supplementary phosphorus source includes one or more of NH4H2PO4, (NH4)2HPO4, (NH4)3PO4, LiHPO4, H3PO4, and FePO4; The supplementary iron source is one or more of Fe2O3, FePO4, FeC2O4•2H2O, FeSO4, and Fe(NO3)3.

[0010] Furthermore, the supplementary carbon source includes one or more of glucose, sucrose, starch, citric acid, graphite, asphalt, acetylene black and graphene; The complexing agent includes one or more of sulfosalicylic acid, triethanolamine, EGTA, ethylenediaminetetrapropionic acid, triethylenetetramine, EDTA, citric acid and oxalic acid.

[0011] Furthermore, the lithium iron phosphate waste powder includes one or more of lithium iron phosphate positive electrode materials from waste batteries, waste materials from the lithium iron phosphate production process, waste electrodes from the preparation of lithium iron phosphate electrodes, or crushed positive electrode materials.

[0012] Furthermore, it is characterized in that the sequential dissolution in step S1 is carried out under the condition of pH 3-7, and the pH adjuster includes one of hydrochloric acid, nitric acid, phosphoric acid and sulfuric acid.

[0013] Furthermore, the purification treatment in step S2 includes demagnetization, crushing and refinement, and the crushing and refinement adopt one or more of split flow crushing and ball milling, and the D50 of the lithium iron phosphate powder after crushing and refinement is controlled at 0.05~1.5μm.

[0014] Furthermore, the stirring in step S2 includes one of magnetic stirring, ball milling stirring and sand milling.

[0015] Furthermore, the drying in step S3 includes one or more of natural drying, vacuum drying, spray drying and freeze drying.

[0016] Furthermore, the multi-stage sintering in step S3 includes a pre-sintering stage at a temperature of 350-500° C. and a qualitative sintering stage at 650-1000° C., the pre-sintering time is 2-10 hours, and the qualitative sintering time is 2-20 hours.

[0017] The present invention has the following beneficial effects in the actual production process: The deactivated lithium iron phosphate crystals are repaired by mixing and impregnating in the sol liquid and then sintering at high temperature. The carbon layer material and the solid electrolyte form an in-situ coating or composite on the surface, pore structure or grain boundary of the lithium iron phosphate.

[0018] The use of solid electrolyte composite or coating can improve the ionic conductivity of the positive electrode active material and accelerate the transmission rate of lithium ions inside and on the surface of the crystal. The solid electrolyte coating can protect the active material to avoid being corroded by direct contact with the electrolyte.

[0019] Composite or encapsulation with solid electrolytes can be applicable to both liquid and solid-state batteries.

[0020] By using a composite or coated solid electrolyte, the lithium-containing solid electrolyte can replenish lithium to the repaired LFP and optimize the CEI membrane structure, thereby improving the stability of the battery.

[0021] The addition of the carbon coating layer is beneficial to improving electronic conductivity, facilitating electron conduction, reducing polarization and battery impedance, and improving battery rate performance.

[0022] The obtained and collected lithium iron phosphate / solid electrolyte / carbon composite material has the characteristics that the solid electrolyte and the carbon layer grow in situ on the surface, pore structure and grain boundary of the lithium iron phosphate, forming a solid electrolyte and carbon mixed layer co-coated, a solid electrolyte composite and a carbon layer coated, a solid electrolyte inner layer and a carbon outer layer, a solid electrolyte outer layer and a carbon inner layer, or a solid electrolyte outer layer and a carbon inner layer distributed on the surface or internal structure of the lithium iron phosphate particles to form a lithium iron phosphate / solid electrolyte / carbon composite material. In summary, the in-situ generated oxide solid electrolyte and carbon material double coated or composite lithium iron phosphate particles are conducive to optimizing the electronic conductivity and ionic conductivity of the lithium iron phosphate material, efficiently activating and repairing defective lithium iron phosphate, and realizing the recycling of waste lithium iron phosphate powder in energy storage batteries and power batteries. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0024] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.

[0026] A method for recovering and repairing defective lithium iron phosphate products comprises the following steps: S1. After dissolving solid electrolyte raw materials, supplementary lithium source, supplementary phosphorus source and supplementary iron source in sequence, supplementary carbon source and complexing agent are added to obtain a reaction sol.

[0027] The solid electrolyte raw material includes one of an oxide solid electrolyte, a sulfide solid electrolyte and a halide electrolyte; The oxide solid electrolyte includes any one of NASICON solid electrolyte, garnet solid electrolyte, and perovskite electrolyte, including but not limited to Li7La3Zr2O 12 (LLZO), Li 6.75 LqCy 1.75 Ta 0.25 O 12 (LLZTO), Li 3x La 2 / 3-xTiO3(LLTO), Li3BO3(LBO), Li 1+x Al x Ti 2-x (PO4)3(LATP); Furthermore, the aforementioned solid electrolyte has the following characteristics: a. The conductivity of the solid electrolyte is greater than 10-5 S / cm; b. The theoretical oxidation potential of the solid electrolyte is greater than 4.2 V.

[0028] Sulfide solid electrolytes include Li 10 GeP2S 12 、Li6PS5Cl、Li 10 S N 12 , one or more of Li2S-P2S5, Li2S-SiS2 and Li2S-B2S3; The halide solid electrolyte includes one or more of Li3YCl6, Li3ErCl6, Li3YBr6, Li3InBr and Li3InCl6.

[0029] Specifically, for other added components, the supplementary lithium source includes one or more of Li2CO3, LiOH, LiHPO4, LiNO3, lithium acetate, lithium citrate, LiF and LiCl; The supplementary phosphorus source includes one or more of NH4H2PO4, (NH4)2HPO4, (NH4)3PO4, LiHPO4, H3PO4, and FePO4; The supplementary iron source is one or more of Fe2O3, FePO4, FeC2O4•2H2O, FeSO4, and Fe(NO3)3.

[0030] Furthermore, the supplementary carbon source includes one or more of glucose, sucrose, starch, citric acid, graphite, asphalt, acetylene black and graphene; The complexing agent includes one or more of sulfosalicylic acid, triethanolamine, EGTA, ethylenediaminetetrapropionic acid, triethylenetetramine, EDTA, citric acid and oxalic acid.

[0031] In this step, the pH environment for mixing and dissolving the raw materials is controlled at 3-7.

[0032] S2. Add the purified lithium iron phosphate waste powder into the reaction sol and stir to form a pre-sizing material.

[0033] The purification treatment mentioned here includes demagnetization, crushing and refinement. The crushing and refinement adopt one or more of split flow crushing and ball milling. The D50 of the lithium iron phosphate powder after crushing and refinement is controlled at 0.05~1.5μm.

[0034] Furthermore, the stirring here includes one of magnetic stirring, ball milling stirring and sand milling.

[0035] At the same time, the waste lithium iron phosphate powder here includes one or more of waste battery lithium iron phosphate positive electrode materials, waste materials from the lithium iron phosphate production process, waste electrodes for the preparation of lithium iron phosphate electrodes, or broken positive electrode materials.

[0036] S3. Dry the pre-sizing material, perform multi-stage sintering, and then crush it to obtain a lithium iron phosphate / solid electrolyte / carbon composite material as a repaired product.

[0037] Finally, the drying here includes one or more of natural drying, vacuum drying, spray drying and freeze drying.

[0038] When sintering the material, the multi-stage sintering includes a pre-sintering stage at a temperature of 350~500°C and a qualitative sintering stage at 650~1000°C. The pre-sintering time is 2~10h and the qualitative sintering time is 2~20h.

[0039] The following is a further description using specific embodiments.

[0040] Example 1 1) Treatment of waste powder of waste lithium iron phosphate cathode materials The waste lithium iron phosphate electrode material is alkali washed and mechanically crushed to obtain waste lithium iron phosphate powder material with a particle size of less than 10μm, and then heat treated at 350℃ for 2h under an inert atmosphere to fully decompose the PVDF bonding material therein; the obtained waste lithium iron phosphate material is then solid-phase ball milled and air flow crushed to obtain waste lithium iron phosphate powder particles with D50, 500nm.

[0041] (2) Li2CO3 (51.91 g), La2O3 (10.95 g), ZrO2 (5.58 g) and NH4H2PO4 (143.40 mL) were stirred, and diluted hydrochloric acid HCl was added to gradually dissolve the solid matter, and a transparent solution with a pH of 4.5-6 was obtained. Subsequently, 20.0 g of sucrose was added to the solution as a supplementary carbon source and a complexing agent for chelation, and a colloidal solution was obtained by continuous stirring. Then, 1870 g of the treated lithium iron phosphate nanopowder was added to the colloidal solution and continuously mixed in a sand mill. The obtained uniform slurry was spray dried to obtain a precursor. The obtained precursor was placed in a box furnace and sintered in stages in a nitrogen flow atmosphere, first sintered at 450 ° C for 4 h, then heated to 780 ° C for sintering, and kept warm for 10 h. After the insulation was completed, it was naturally cooled to room temperature, and after air flow pulverization, LiFePO4 / Li7La3Zr2O 12 / C (LFP / LLZO / C) positive electrode material, particle size D50 is about 0.956mm.

[0042] The obtained LFP / LLZO / C has the characteristics of having LFP as a core, LLZO as an inner coating layer and a carbon material as a composite material of the outermost coating layer.

[0043] Example 2 Compared with Example 1, step 2) is: Dissolve LiNO3 (84.69g), La2O3 (10.79g), TiO2 (9.28g) and NH4H2PO4 (114.1g) in 1500mL of deionized water, and add HCl to adjust the pH until the solid matter is completely dissolved; then add tartaric acid (C4H6O6) and stir continuously to form a clear solution. Add 1500g of lithium iron phosphate waste powder treated in the same way as in Example 1, stir continuously, and perform sand milling. Spray dry the obtained slurry to obtain a precursor. Pre-sinter the obtained precursor at 400℃ for 5h in a nitrogen flowing atmosphere; then keep it at 800℃ for 6h, cool it naturally to room temperature, and collect it after crushing. 0.33 La 0.57 The composite material of TiO3 / C (LFP / LLTO / C) has a particle size D50 of about 1.026 mm.

[0044] The material characteristic of LFP / LLTO / C is that a mixed layer of LLTO and carbon material co-coats LFP.

[0045] Example 3 Compared with Example 1, step 2) is: Dissolve 5.80g of tetrabutyl titanate in a mixture of deionized water (500mL) and ethanol (100mL) and stir. Add Li2CO3 (0.45g), Al(NO3)3•9H2O (1.128g), and NH4H2PO4 (1.15g). Use HNO3 to adjust the pH of the solution so that the solid matter is completely dissolved. Then spray the prepared solution on the prepared 1000g of lithium iron phosphate residues for impregnation. Then freeze-dry to obtain a dry precursor. Then pre-sinter the precursor at 450℃ for 5h in a nitrogen flow atmosphere, then heat to 815℃ and keep warm for 7h; naturally cool to room temperature, grind and collect to obtain LiFePO4 / Li 1.2 Al 0.3 Ti 1.7 (PO4)3 / C (LFP / LATP / C) composite materials.

[0046] The LFP / LATP / C composite material is characterized by a composite material having LFP as a core, a carbon layer as a middle layer and LATP as an outermost layer.

[0047] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that only a supplementary lithium source Li2CO3, a supplementary phosphorus source NH4H2PO4 and a supplementary carbon source sucrose are added, and only one-step sintering is performed, the sintering temperature is 780°C, and the insulation time is 10 hours to obtain LFP material.

[0048] Comparative Example 2 Use defective LFP obtained from large-scale production.

[0049] The composite materials prepared in each embodiment were tested for physical properties and electrochemical performance, wherein the carbon content was tested by a carbon-sulfur analyzer; the particle size was tested by a laser particle size analyzer; the electronic conductivity was tested by a four-probe method; the ionic conductivity was tested by assembling a symmetrical cell at 25°C for EIS test, and the calculation was performed in combination with the corresponding ionic conductivity formula; the composite materials obtained in each embodiment were assembled into button cells according to the following method: the composite material, conductive carbon black and adhesive polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 95:5:5, N-methylpyrrolidone was used as a solvent, and the slurry was evenly coated on an aluminum foil, dried at 100°C for 12 hours, and compacted to obtain a positive electrode sheet, the mass of the active material of the positive electrode sheet was about 12 mg. The negative electrode used a metal lithium sheet, the diaphragm was a polypropylene porous membrane, and the electrolyte was 1 mol / L LiPF6 / EC+DEC+DMC (volume ratio EC:DEC:DMC=1:1:1). The voltage range of the button battery charge and discharge test is 2.00-3.75V.

[0050] The specific results are as follows, wherein Table 1 shows the physicochemical properties of the materials in different embodiments and comparative examples, and Table 2 shows the electrochemical properties of the materials in different embodiments and comparative examples.

[0051] Table 1: Example Finished Product <![CDATA[Compaction density (g / cm 3 ).]]> Resistivity (Ω·cm) Ionic conductivity (S / cm) Example 1 LFP / LLZO / C 2.36 3.52 <![CDATA[5.5×10 -3 ]]> Example 2 LFP / LLTO / C 2.45 4.37 <![CDATA[3.5×10 -2 ]]> Example 3 LFP / LATP / C 2.43 4.65 <![CDATA[9.2×10 -3 ]]> Comparative Example 1 LFP / C 2.28 12.78 <![CDATA[3.8×10 -6 ]]> Comparative Example 2 LFP / C 2.34 14.23 <![CDATA[3.4×10 -6 ]]> Table 2: Example Finished Product 1C specific capacity (mAh / g) First coulombic efficiency (%) 200 cycles retention rate (%) 5C specific capacity (mAh / g) Example 1 LFP / LLTO / C 146.8 101.2 97.6 115.3 Example 2 LFP / LLZO / C 143.6 103.6 98.2 108.6 Example 3 LFP / LATP / C 148.3 101.3 98.6 122.5 Comparative Example 1 LFP / C 131.2 98.6 94.3 76.3 Comparative Example 2 LFP / C 136.6 99.2 95.6 72.4 It can be seen from the data in the above table that, compared with Comparative Example 1, only the waste lithium iron phosphate waste powder is repaired at high temperature. The electronic conductivity and ionic conductivity of the materials after the inorganic solid electrolyte and carbon coating are compounded in Example 1 and Example 2 are significantly improved, indicating that the joint compound of the inorganic solid electrolyte and the carbon material can simultaneously improve the conductivity of the waste lithium iron phosphate powder material. At the same time, the active lithium is activated and the crystal structure is repaired to achieve the purpose of optimizing its electrochemical properties. Comparative Example 2 is a substandard defective product obtained by high-temperature sintering. After the modified sample was composited with an inorganic solid electrolyte and a carbon material in Example 3, there was a large difference in the discharge specific capacity at 1 C and 5 C, indicating that the joint compound of the solid electrolyte and the carbon material promotes the material structure repair and electrochemical performance optimization of the waste lithium iron phosphate powder.

[0052] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for recovering and repairing defective lithium iron phosphate products, characterized in that: The following steps are involved: S1. After dissolving the solid electrolyte raw material, the supplementary lithium source, the supplementary phosphorus source and the supplementary iron source in sequence, a supplementary carbon source and a complexing agent are added to obtain a reaction sol; S2. The purified lithium iron phosphate waste powder is added to the reaction sol and stirred to form a pre-sizing material; S3. Dry the pre-sizing material, perform multi-stage sintering, and then crush it to obtain a lithium iron phosphate / solid electrolyte / carbon composite material as a repaired product.

2. The method for recovering and repairing defective lithium iron phosphate products according to claim 1, characterized in that: The solid electrolyte raw material includes one of an oxide solid electrolyte, a sulfide solid electrolyte and a halide electrolyte; The oxide solid electrolyte includes any one of a NASICON solid electrolyte, a garnet solid electrolyte, and a perovskite solid electrolyte; The sulfide solid electrolyte includes Li 10 GeP2S 12 、Li6PS5Cl、Li 10 S N 12 , one or more of Li2S-P2S5, Li2S-SiS2 and Li2S-B2S3; The halide solid electrolyte includes one or more of Li3YCl6, Li3ErCl6, Li3YBr6, Li3InBr and Li3InCl6.

3. The method for recovering and repairing defective lithium iron phosphate products according to claim 1, characterized in that: The supplementary lithium source includes one or more of Li2CO3, LiOH, LiHPO4, LiNO3, lithium acetate, lithium citrate, LiF and LiCl; The supplementary phosphorus source includes one or more of NH4H2PO4, (NH4)2HPO4, (NH4)3PO4, LiHPO4, H3PO4, and FePO4; The supplementary iron source is one or more of Fe2O3, FePO4, FeC2O4•2H2O, FeSO4, and Fe(NO3)3.

4. The method for recovering and repairing defective lithium iron phosphate products according to claim 1, characterized in that: The supplementary carbon source includes one or more of glucose, sucrose, starch, citric acid, graphite, asphalt, acetylene black and graphene; The complexing agent includes one or more of sulfosalicylic acid, triethanolamine, EGTA, ethylenediaminetetrapropionic acid, triethylenetetramine, EDTA, citric acid and oxalic acid.

5. The name according to claim 1, characterized in that: The method for recycling and repairing defective lithium iron phosphate products according to claim 1 is characterized in that the lithium iron phosphate waste powder includes one or more of waste battery lithium iron phosphate positive electrode materials, lithium iron phosphate production process waste, lithium iron phosphate electrode sheet preparation waste electrode sheets or broken positive electrode materials.

6. A method for recovering and repairing defective lithium iron phosphate products according to any one of claims 1 to 5, characterized in that: The sequential dissolution in step S1 is performed under a pH condition of 3-7, and the pH adjuster includes one of hydrochloric acid, nitric acid, phosphoric acid and sulfuric acid.

7. A method for recovering and repairing defective lithium iron phosphate products according to any one of claims 1 to 5, characterized in that: The purification treatment in step S2 includes demagnetization, crushing and refining. The crushing and refining adopt one or more of split flow crushing and ball milling. The D50 of the lithium iron phosphate powder after crushing and refining is controlled to be 0.05-1.5 μm.

8. A method for recovering and repairing defective lithium iron phosphate products according to any one of claims 1 to 5, characterized in that: The stirring in step S2 includes one of magnetic stirring, ball milling stirring and sand milling.

9. A method for recovering and repairing defective lithium iron phosphate products according to any one of claims 1 to 5, characterized in that: The multi-stage sintering in step S3 includes a pre-sintering stage at a temperature of 350-500° C. and a qualitative sintering stage at a temperature of 650-1000° C. The pre-sintering time is 2-10 hours, and the qualitative sintering time is 2-20 hours.